Biological synthesis of silver nanoparticles using the fungus humicola sp and evaluation of their cytoxicity using normal and cancer cell lines - Syed, Asad; Saraswati, Supriya; Kundu, Gopal C.; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
Nanoscience is a new born science of the modern era and taps into the potential of particles at nanoscale. Bulk materials reduced to nanoscale dimensions thus obtain unique properties such as electronic, optical, magnetic and chemical. As far as synthesis of nanoparticles is concerned, biological synthesis has recently sparked a great interest as compared to other available chemical and physical methods on account of its eco-friendliness and cost-effectiveness. Here we report, for the first time, the biosynthesis of silver nanoparticles by the thermophilic fungus Humicola sp. The fungus when reacted with Ag+ ions reduces the precursor solution and leads to the formation of extracellular nanoparticles as monitored by ultra violet visible spectroscopy (UV-Vis). The morphology of nanoparticles is found to be spherical with good dispersity as revealed by transmission electron microscopy (TEM). Cell viability assays were carried out to assess the cytotoxicity of silver nanoparticles on NIH3T3 mouse embryonic fibroblast cell line and MDA-MB-231 human breast carcinoma cell line. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Fungus; Humicola sp.; Nanoparticles; Silver